Use of Medicinal and Aromatic Plant Residues for Partial Peat Substitution in Growing Media for Sonchus oleraceus Production - Chrysargyris, Antonios; Goumenos, Christos; Tzortzakis, Nikos G. (My University, 2023)
A substantial quantity of solid waste that is high in phenolics and biocomponents is produced during the industrial manufacturing of essential oils (EOs); this presents an important management challenge for the EO sector. This currently produces a significant amount of residue, causing issues of disposal and management and the impact that the residues have on both the environment and human health. The present study evaluated the potential use of Origanum dubium Boiss. residues (ODR) and Sideritis cypria Post. residues (SCR) derived via distillation at different levels (0–5–10–20–40% v/v) for use in partial peat substitution in the production of Sonchus oleraceus L. (sowthistle) plants. Both ODR and SCR accelerated the pH, electrical conductivity, organic matter content, and mineral content of the growing media, but also negatively affected several of the physical characteristics of the media, such as the total porosity and aeration. This resulted in decreased plant growth, which was more noticeable at the high residue ratios. Plants responded to this by decreasing the leaf stomatal conductance, decreasing the chlorophyll content at 40% ODR and 20% SCR mixtures, and activating several non-enzymatic (phenols, flavonoids, and antioxidant capacity) and enzymatic (superoxide dismutase) mechanisms to challenge the observed stress conditions, as indicated by lipid peroxidation and the hydrogen peroxide increase. Plants grown in residue media exhibited changes in mineral accumulation, even though both ODR and SCR were rich in minerals. It may be concluded that ODR and SCR, when employed at low levels of 10% and 20%, respectively, have the potential for use in the preparation of growing media as they may increase plant material antioxidants, but further improvement of the growing media’s properties is needed to ensure adequate yield.
Keywords: Sowthistle; Distillation; Plant growth; Peat; Wild edible species; Minerals